Identificação dos impactos da covid-19 no diagnóstico e no tratamento da tuberculose pulmonar no Maranhão - FONSECA, Dayane Thalia Pires (2024)
Introduction: Tuberculosis (TB) became the leading cause of death from infectious diseases worldwide in 2015. Among other diseases that can affect the lungs, there is COVID-19. Coinfection by TB and COVID-19 has been studied and evaluated regarding the hypothesis that both may exacerbate each other's natural symptoms, as well as interfere with the diagnosis and treatment of one another. Objective: To identify the impacts of COVID-19 on the diagnosis and treatment of pulmonary tuberculosis in patients at the Presidente Vargas Hospital in São Luís, MA. Methodology: This is a retrospective observational cohort study, carried out from April to August 2023, at Hospital Presidente Vargas de São Luís-MA. Patients admitted to the hospital with isolated pulmonary tuberculosis and concomitant COVID-19 infection were evaluated, from January 2019 to December 2021. Data were tabulated and organized in Microsoft Office Excel® and analyzed in SPSS (v. 16 ). All statistical associations were set at significance p < 0.05. ‘Results: The study analyzed data from 74 medical records of patients with pulmonary TB in the pre-pandemic period (n=33) and during the first two years of the pandemic (n=41). Additionally, 12 patients with a diagnosis of TB coinfected with COVID-19 were evaluated. In the group with pulmonary tuberculosis, in both periods, there was a predominance of individuals aged 40 to 59 years (51,4%), males (60,8%), of brown skin color (81,1%), single (82,4%), with incomplete primary education (31,7%), of Catholic religion (62,8%), with a family income of up to one minimum wage (45,3%), and with hypertension or diabetes (18,9%). The most common symptoms presented by TB patients did not show significant differences between the periods, with cough (90,5%) and weight loss (75,7%) being the main ones. The presence of "tree-in-bud" pattern on Chest Tomography was significant during the pandemic period (79, 4%, p < 0.001). The predominant outcome was discharge in 83, 8% of cases. Regarding patients with coinfection (n=12), there was a statistically significant difference only in the religion variable (p=0.025). There was also a predominance of individuals aged 34 to 44 years (41,7%), with a mean age of 39,9 (±10.3) years, male (83,3%), of brown skin color (66,7%), single (83,3%), with incomplete primary education (40,0%), of Catholic religion (50,0%), with a family income of up to one minimum wage (60,0%), and with hypertension or diabetes in only 8,3% of patients in both comorbidities. Chest computed tomography with tree-in-bud pattern prevailed as a diagnostic tool in 80% of cases, followed by positive direct bacilloscopy (62,5%). The most common symptoms presented by TB/COVID-19 coinfected patients were dyspnea (75,0%) and fever (66,7%) and the RT-PCR serology (75,0). The outcome was discharge in 66,7% of cases. Conclusion: There was no interference of the COVID-19 pandemic on the diagnosis and treatment of patients with pulmonary tuberculosis.